2004
DOI: 10.1292/jvms.66.1503
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Equine Coital Exanthema in Pastured Draft Horses and Isolation of Equine Herpesvirus 3 from Progenital Lesions

Abstract: ABSTRACT. During the period from 2001 to the following year, progenital diseases had been epidemic among the draft stallions and mares pastured together in Iwate Prefecture, the northeastern district of Japan. A stallion and 8 of 31 mares were affected in 2001, and 1 of 2 stallions and 10 of 36 mares in 2002. The clinical symptoms consisted of the formation of papules, pustules, ulcers and scabs on the progenital skin and mucosa in stallions and mares. In 2002, Equine herpesvirus 3 (EHV3) was isolated from 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
2
23
1
3
Order By: Relevance
“…A topical experimental infection with EHV-3 was able to produce ECE clinical signs, which were closely similar to those previously described during field outbreaks (Barrandeguy, 2010;Tibary and Fite, 2007 Seki et al, 2004). This experimental model was even able to produce clinical signs and virus shedding in seropositive (previously infected) mares.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A topical experimental infection with EHV-3 was able to produce ECE clinical signs, which were closely similar to those previously described during field outbreaks (Barrandeguy, 2010;Tibary and Fite, 2007 Seki et al, 2004). This experimental model was even able to produce clinical signs and virus shedding in seropositive (previously infected) mares.…”
Section: Discussionsupporting
confidence: 85%
“…To detect and quantify EHV-3, an adapted quantitative real time PCR assay, targeting a region of the EHV-3 gG gene as shown by Seki et al (2004), was carried out (Barrandeguy et al, 2008). Quantification of EHV-3 in the PVS was calculated by generating a standard curve with log dilutions of the reference strain containing 10 6.50 TCID 50 / ml and expressed as TCID 50 equivalents.…”
Section: Ehv-3 Detection and Measurement Of Virus Excretion By Quantimentioning
confidence: 99%
“…The presence of infection has been reported in Australia, Argentina, Austria, Canada, Denmark, Norway, the US, the UK, Japan, India, and Mongolia (1,2,4,7,8,11,(14)(15)(16). The seroprevalence of EHV-3 is about 18%-53% around the world (4,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the infection is widespread in embryo transfer and in horse breeding centres around the world where the prevalence varies from 6%-58% (2,(8)(9)(10), although there have been limited reports on the prevalence of EHV-3 in working horses (1,11). The purpose of this study was to investigate the seroprevalence of EHV-3 in various horse populations in Turkey, for which there was no information available, in an effort to assess the regional baseline infection/disease prevalence rate and to guide future epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…말구진은 19세기와 20세기 초반에 유럽에서 발생하고 있었 고 [23] 1968년 캐나다 [8]와 미국에서 처음으로 EHV-3를 분리 하였다 [2,5]. 그 후 전 세계에서 발생하고 있으며 [17,23], 일본 에서도 발생되었으나 [20] 아직 국내의 보고는 없었다. …”
Section: Comparison Of the Nucleotide Sequences Of Gg Gene From Ehv-3unclassified